Business process management forum : BPM Forum 2018, Sydney, NSW, Australia, September 9-14, 2018, Proceedings /: BPM Forum 2018, Sydney, NSW, Australia, September 9-14, 2018, Proceedings. (2018) - Unknown
No abstract available